Ipomoviruses - Webb, S.E.; Adkins, S.; Maruthi, M.N.; Legg, James P. (Scientific Societies, 2016)
The Ipomovirus genus in the family Potyviridae contains five species: Sweet potato mild mottle virus (SPMMV), Squash vein yellowing virus (SqVYV), Cucumber vein yellowing virus (CVYV), Cassava brown streak virus (CBSV), and Ugandan cassava brown streak virus (UCBSV). Sequencing and analysis of Tomato mild mottle virus (TomMMoV), a currently unassigned species in Potyviridae,suggest that it may also be an ipomovirus. This chapter focuses on Squash vein yellowing virus (SqVYV), Cucumber vein yellowing virus (CVYV), and Cassava brown streak virus (CBSV).